Sufi Feminist Hermeneutics in Ibn ‘Ajībah’s Tafsīr on the Discourse of Gender-Related Verses - Rofi'ah, Khofidatur; Kerwanto, Kerwanto; Budiman, Ikhlas (An-Nida', 2025)
This study seeks to analyze the construction of meanings in gender-related verses within al-Baḥr al-Madīd, a Qur’anic exegesis authored by Ibn ‘Ajībah, through the lens of feminist hermeneutics. The research is motivated by the paucity of scholarship that bridges Sufi epistemology and Islamic feminist discourse, particularly in exploring the interplay between ẓāhir (literal) and bāṭin (inner) meanings in Sufi interpretations of verses addressing relations between men and women. Utilizing a qualitative-descriptive methodology with a textual analysis approach, this study examines Ibn ‘Ajībah’s interpretive framework alongside the epistemological foundations underpinning his exegetical method. The analysis centers on the influence of Sufi spiritual values—such as spiritual equality, purification of the soul, and respect for human dignity—in shaping the interpretation of gender-related verses and their potential to facilitate more inclusive readings concerning women’s rights. The findings reveal that the ishārī approach employed by Ibn ‘Ajībah foregrounds ethical and spiritual dimensions that enable non-hierarchical reinterpretations of gender-related verses. Nonetheless, these interpretations remain engaged with ẓāhir meanings, which are informed by the social context and scholarly traditions of his era. This study demonstrates that Sufi exegesis constitutes a significant alternative framework for advancing gender equality discourse within Qur’anic studies, while simultaneously broadening the scope of Islamic feminism to encompass Sufi spirituality.Abstrak: Penelitian ini bertujuan menganalisis konstruksi pemaknaan ayat-ayat gender dalam tafsir al-Baḥr al-Madīd karya Ibn ‘Ajībāh melalui perspektif hermeneutika feminis. Kajian ini berangkat dari minimnya penelitian yang mengaitkan epistemologi sufistik dengan wacana feminisme Islam, khususnya dalam menelaah relasi antara makna ẓāhir dan bāṭin dalam tafsir sufistik terhadap ayat-ayat yang berkaitan dengan relasi laki-laki dan perempuan. Penelitian ini menggunakan metode kualitatif-deskriptif dengan pendekatan analisis teks untuk menelusuri cara kerja penafsiran Ibn ‘Ajībāh serta kerangka epistemologis yang melandasinya. Fokus analisis diarahkan pada peran nilai-nilai spiritualitas sufi, seperti kesetaraan spiritual, penyucian jiwa, dan penghormatan terhadap martabat manusia dalam membentuk pemaknaan ayat-ayat gender serta potensinya dalam membuka ruang pembacaan yang lebih inklusif terhadap hak-hak perempuan. Hasil penelitian menunjukkan bahwa pendekatan isyārī yang digunakan Ibn ‘Ajībāh menekankan dimensi etis dan spiritual yang memungkinkan reinterpretasi non-hierarkis terhadap ayat-ayat gender. Namun demikian, penafsiran tersebut tetap berinteraksi dengan makna ẓāhir yang dipengaruhi oleh konteks sosial dan tradisi keilmuan pada masanya. Temuan ini menegaskan bahwa tafsir sufistik memiliki kontribusi signifikan sebagai rujukan alternatif dalam pengembangan wacana kesetaraan gender dalam studi Al-Qur’an, sekaligus memperluas horizon feminisme Islam ke dalam ranah spiritualitas sufistik.